Mixed silver powder, method for producing mixed silver powder, and conductive paste
A mixed silver powder with specific particle ratios and polyhydric carboxylic acid treatment addresses the issue of high resistance in conductive films, enhancing conductivity and reducing porosity.
Patent Information
- Application Number
- JP2024084323
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-05-31
- Filing Date
- 2024-05-23
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2044-05-23
AI Technical Summary
Conventional conductive pastes using silver powder fail to adequately reduce the specific resistance of conductive films, which is necessary for advanced electronic devices.
A mixed silver powder composition comprising primary, secondary, and tertiary silver particles with specific aspect ratios and surface treatment with polyhydric carboxylic acids to enhance conductivity.
The mixed silver powder significantly reduces the specific resistance of conductive films, improving conductivity and filling properties, leading to denser films with lower resistance.
Smart Images

Figure 0007606642000005 
Figure 0007606642000006 
Figure 0007606642000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a mixed silver powder, a method for producing the mixed silver powder, and a conductive paste. [Background technology]
[0002] A method of applying or printing a conductive paste containing a conductive metal powder onto a substrate such as a film, a board, or an electronic component, and then drying and curing the paste by heating has been widely used to form electrodes, electrical wiring, etc. However, with the recent trend toward higher performance of electronic devices, electrodes, electrical wiring, etc. formed using the conductive paste are required to have lower resistance, and this requirement is becoming stricter every year.
[0003] In response to the above demands, for example, Patent Document 1 proposes the use of a silver powder consisting of a flaky silver powder and a spherical silver powder, in which a polyvalent carboxylic acid is adhered to the surface of at least one of the flaky silver powder and the spherical silver powder, as a conductive metal powder, in order to obtain a conductive paste composition having high conductivity (low resistance). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-100573 A Summary of the Invention [Problem to be solved by the invention]
[0005] Here, for the silver powder (silver powder) that can be used in conventional conductive pastes, there is room for further improvement in terms of reducing the resistivity of the conductive film formed using the conductive paste.
[0006] Therefore, an object of the present invention is to provide a mixed silver powder capable of reducing the resistivity of a conductive film. Another object of the present invention is to provide a method for producing a mixed silver powder that can reduce the resistivity of a conductive film. Another object of the present invention is to provide a conductive paste capable of reducing the resistivity of a conductive film. [Means for solving the problem]
[0007] As a result of extensive research by the inventors to solve the above-mentioned problems, the inventors have completed the present invention described below.
[0008] That is, the gist of the present invention for solving the above-mentioned problems is as follows.
[0009] [1] A mixed silver powder consisting of first silver particles, second silver particles, and third silver particles, Observing 100 or more silver particles on a polished cross section of a resin block in which the mixed silver powder is embedded in resin, The perimeter of the silver particle; and When the long side length and the short side length of a rectangle that circumscribes the outer shape of the silver particles and has the smallest area are measured, The silver particles having a long side length of 3 μm or more are called first silver particles. The silver particles having a long side length of 0.5 μm or more and less than 3 μm are called second silver particles. The silver particles having a long side length of less than 0.5 μm are called third silver particles. In this case, the first silver particles have an average aspect ratio of 2 or more, the average aspect ratio of the second silver particles is 1.5 or more and less than 2, the average aspect ratio of the third silver particles is less than 1.5; the number ratio of the first silver particles in the mixed silver powder is 0.5% or more and 5% or less, the number ratio of the second silver particles is 10% or more, and the number ratio of the tertiary silver particles is 15% or more, The following formula (1): Ratio α = peripheral length of secondary silver particle / (long side length of secondary silver particle × 2 + short side length of secondary silver particle × 2) (1) The average value of the ratio α calculated by is 0.84 or more, The mixed silver powder has a polyvalent carboxylic acid attached to the surface of at least one type of silver particle selected from the group consisting of the first silver particles, the second silver particles, and the third silver particles.
[0010] [2] The mixed silver powder according to [1], in which a polyvalent carboxylic acid is attached to the surfaces of the first silver particles and the second silver particles.
[0011] [3] The mixed silver powder according to [1] or [2], wherein the content of the polyvalent carboxylic acid relative to the total content of the first silver particles, the second silver particles, and the tertiary silver particles is 0.01 mass% or more and 0.15 mass% or less.
[0012] [4] The mixed silver powder according to any one of [1] to [3], wherein the polycarboxylic acid is at least one polycarboxylic acid selected from the group consisting of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, malic acid, diethylglutaric acid, 3-methyladipic acid, butylmalonic acid, maleic acid, diglycolic acid and citric acid.
[0013] [5] a mixing step of mixing silver powder A containing silver particles A1 and silver particles A2 with silver powder B containing silver particles B to obtain a mixture; a pretreatment step in which at least one of the silver powders A and B is treated with a polycarboxylic acid to adhere a surface treatment agent thereto before the mixing step, or a posttreatment step in which the mixture obtained in the mixing step is treated with a polycarboxylic acid to adhere a surface treatment agent thereto; Including, Observing 100 or more silver particles on a polished cross section of a resin block in which the silver powder A is embedded in a resin, and observing 100 or more silver particles on a polished cross section of a resin block in which the silver powder B is embedded in a resin, The perimeter of the silver particle; and the long side length and the short side length of a rectangle that circumscribes the outer shape of the silver particle and has the smallest area, When measuring, The silver particles A1 have an average aspect ratio of 2 or more, The silver particles A2 have an average aspect ratio of less than 2, and The following formula (2): Ratio β = perimeter of silver particle A2 / (long side length of silver particle A2 × 2 + short side length of silver particle A2 × 2) (2) The average value of the ratio β calculated by is 0.84 or more, The method for producing a mixed silver powder according to any one of [1] to [4], wherein the silver particles B have an average aspect ratio of less than 1.5.
[0014] [6] Including the pretreatment step, The method for producing a mixed silver powder according to [5], wherein in the pretreatment step, the silver powder A is treated with the polyvalent carboxylic acid to adhere a surface treatment agent thereto.
[0015] [7] A method for producing a mixed silver powder according to [5] or [6], wherein the usage rate of the polyvalent carboxylic acid relative to the total of the silver powder A and the silver powder B is 0.01 mass% or more and 0.15 mass% or less.
[0016] [8] The method for producing a mixed silver powder according to any one of [5] to [7], wherein the polyvalent carboxylic acid used in the surface treatment agent adhesion treatment is at least one polyvalent carboxylic acid selected from the group consisting of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, malic acid, diethylglutaric acid, 3-methyladipic acid, butylmalonic acid, maleic acid, diglycolic acid and citric acid.
[0017] [9] A conductive paste comprising the mixed silver powder according to any one of [1] to [4], a binder, and a solvent. Effect of the Invention
[0018] According to the present invention, a mixed silver powder capable of reducing the resistivity of a conductive film can be provided. Furthermore, according to the present invention, a method for producing a mixed silver powder capable of reducing the resistivity of a conductive film can be provided. Moreover, according to the present invention, a conductive paste capable of reducing the resistivity of a conductive film can be provided. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a schematic diagram for explaining a method for specifying the long side length and short side length of a rectangle that circumscribes the outer shape of the cross section of a silver particle and has the smallest area. [Diagram 2] 1 is a scanning electron microscope photograph of the mixed silver powder of Example 1. [Diagram 3] 1 is a scanning electron microscope photograph of the mixed silver powder of Example 2. [Figure 4] 1 is a scanning electron microscope photograph of the mixed silver powder of Example 3. [Diagram 5] 1 is a scanning electron microscope photograph of the mixed silver powder of Comparative Example 1. [Figure 6] 1 is a scanning electron microscope photograph of the mixed silver powder of Comparative Example 2. [Figure 7] 1 is a scanning electron microscope photograph of the mixed silver powder of Comparative Example 3. [Figure 8] 1 is a scanning electron microscope photograph of the mixed silver powder of Example 4. [Figure 9] 1 is a scanning electron microscope photograph of the mixed silver powder of Comparative Example 4. [Figure 10] 1 is a scanning electron microscope photograph of the mixed silver powder of Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The mixed silver powder of the present invention is suitable for use as a conductive filler for conductive paste. The conductive paste using the mixed silver powder of the present invention can be used to form a conductive pattern or an electrode on a substrate. The conductive paste using the mixed silver powder of the present invention can be printed on a substrate by, for example, screen printing, offset printing, photolithography, or the like to form a conductive film such as a conductive pattern or an electrode (hereinafter, sometimes simply referred to as a "conductive film"). The mixed silver powder of the present invention can be obtained, for example, by the manufacturing method of the mixed silver powder of the present invention.
[0021] (Terminology and Measurement Methods) Prior to describing the embodiments, the terms and measurement methods used in this specification will be described.
[0022] <Observation of silver particles> In this specification, the silver particles can be observed by first putting the mixed silver powder or silver powder into a resin and a hardener, solidifying the mixture, polishing the mixture with a cross-section polisher to expose the cross-section of the silver particles, and observing each silver particle with a scanning electron microscope (SEM) at a predetermined magnification (e.g., 5,000 times or 3,000 times). Here, due to the contrast between the insulating resin and the conductive silver particles, the outline of the silver particles is clear, and the outer periphery of the silver particles is clearly visible, so that the cross-section is considered to be exposed. Then, for 100 or more silver particles arbitrarily selected from the silver particles whose outer periphery is clearly visible on the polished cross-section of a resin block in which the mixed silver powder or silver powder is embedded in a resin, the long side length of the rectangle (hereinafter may be simply referred to as the "long side length"), the short side length of the rectangle (hereinafter may be simply referred to as the "short side length"), the perimeter, the area of the silver particles, and the maximum length of the silver particles can be measured. As the resin and hardener, for example, "Epofix resin" and "Epofix hardener" manufactured by Struers can be used. As the cross-section polisher, for example, "ArBlade5000" manufactured by Japan High-Technologies Corporation can be used. As the scanning electron microscope, for example, "JEOL JSM-IT300LV" manufactured by JEOL Ltd. can be used. As the image analysis software, for example, "Image Analysis Type Particle Size Distribution Measurement Software Mac-View" manufactured by Mountech Co., Ltd. can be used.
[0023] Here, with reference to FIG. 1, a method for determining the lengths of the long and short sides of a rectangle that circumscribes the outer shape of the cross section of a silver particle and has the smallest area will be described. As shown in Figure 1, first, select silver particles to be measured (100 or more). Next, rotate the selected silver particles 360 degrees to create all rectangles that circumscribe the outline of the silver particles. Then, from these rectangles, select the rectangle with the smallest area, and specify the long and short side lengths of this rectangle.
[0024] <Average aspect ratio> In this specification, "aspect ratio" refers to the ratio of the long side length to the short side length (long side length / short side length), and "average aspect ratio" refers to the average aspect ratio of individual silver particles within a range defined by the long side length value.
[0025] <Average short side length> In this specification, the "average short side length" refers to the average short side length of individual silver particles within a range defined by the long side length value.
[0026] <Average shape factor> In this specification, the "shape factor" means "π × (maximum length of silver particle / 2) 2 The shape factor is calculated by dividing the area of silver particles by the length of the long side. The "average shape factor" is the average value of the individual shape factors of silver particles within a range defined by the value of the long side length. The unit of the maximum length of silver particles is "μm", and the unit of the area of silver particles is "μm 2 "
[0027] <Measurement of particle size distribution> In this specification, the cumulative 10% particle size (D 10 ), cumulative 50% particle diameter (D 50 ), cumulative 90% particle diameter (D 90 ), and cumulative 95% particle size (D 95 ), and the cumulative 100% (i.e., maximum particle) particle diameter (D MAX) was measured using a laser diffraction / scattering particle size distribution analyzer (manufactured by Microtrac Bell Corporation, Microtrac MT-3300 EXII).
[0028] <Method for Measuring Content Ratio of Polycarboxylic Acid> In this specification, the "content ratio of polycarboxylic acid" can be measured by first eluting the polycarboxylic acid from the mixed silver powder with hydrochloric acid, then esterifying the polycarboxylic acid in the hydrochloric acid eluate, then extracting the esterified polycarboxylic acid with an organic solvent, then determining the amount of adipic acid ester extracted from the calibration curve of the polycarboxylic acid ester, and calculating the amount of polycarboxylic acid by conversion calculation. For example, when the polycarboxylic acid is adipic acid, the content ratio of adipic acid can be measured according to the adipic acid quantification method described in JP-A-2012-122880. When the polycarboxylic acid is adipic acid, the content ratio of adipic acid may also be measured by methylating the adipic acid on the surface of the sample silver powder using a hydrogen chloride-methanol reagent, extracting the generated dimethyl adipate with an organic solvent, and measuring it by GC-MS.
[0029] <BET Specific Surface Area> In this specification, the "BET specific surface area" can be measured by the BET one-point method using nitrogen adsorption with Macsorb HM-model 1210 (manufactured by MOUNTECH). In the measurement of the BET specific surface area, the degassing conditions before measurement are 60 °C for 10 minutes.
[0030] <Ignition Loss (Ig-Loss) Value of Mixed Silver Powder> In this specification, the term "Ignition loss (Ig-Loss) value of mixed silver powder" refers to the amount of change in mass when heated from room temperature to 800°C, specifically, the amount of components other than silver contained in the mixed silver powder, and is an index showing the amount of components remaining in the mixed silver powder, such as processing agents and additives used in the manufacturing process of the mixed silver powder. In this specification, the "Ignition loss (Ig-Loss) value of mixed silver powder" can be calculated by precisely weighing a mixed silver powder sample (weighing value: w1), placing it in a magnetic crucible, heating it to 800°C, and holding it at 800°C for 30 minutes, which is a sufficient time to reach a constant weight, then cooling it and reweighing it (weighing value: w2), and calculating the "Ignition loss (Ig-Loss) value (mass%) = (w1-w2) / w1 x 100".
[0031] <Tap density of mixed silver powder> In this specification, the "tap density of the mixed silver powder" can be calculated, for example, by using a tap density measuring device (Shibayama Scientific Co., Ltd., bulk specific gravity measuring device SS-DA-2) to weigh out 30 g of a silver powder sample, place it in a 20 mL test tube, and tap 1,000 times with a drop of 20 mm, as follows: "tap density = sample mass (g) / sample volume after tapping (mL)".
[0032] <Circle equivalent diameter (Heywood diameter)> In this specification, the "circle equivalent diameter (Heywood diameter)" can be calculated using the area of a silver particle measured by observing the cross section of the silver particle. Specifically, the circle equivalent diameter (Heywood diameter) can be calculated by creating a circle having the same area as the area of the silver particle.
[0033] <Viscosity of conductive paste> In this specification, the "viscosity of the conductive paste" may be, for example, the value measured after rotating the cone spindle for 5 minutes using a Brookfield 5XHBDV-IIIUC rotational viscometer and a CPE-52 cone spindle at a measurement temperature of 25°C and a cone spindle speed of 1 rpm.
[0034] (Mixed silver powder) The mixed silver powder of the present invention is a mixed silver powder consisting of first silver particles, second silver particles, and third silver particles, and is obtained by observing 100 or more silver particles on a polished cross section of a resin block obtained by embedding the mixed silver powder in resin, and measuring the perimeter of the silver particles and the long side length and short side length of a rectangle that circumscribes the outer shape of the silver particles and has the smallest area. The silver particles having a long side length of 3 μm or more are called first silver particles, the silver particles having a long side length of 0.5 μm or more and less than 3 μm are called second silver particles, and the long side length and short side length of a rectangle that circumscribes the outer shape of the silver particles and has the smallest area are called first silver particles, second silver particles, and third silver particles, respectively. In the case where silver particles having a length of less than 0.5 μm are regarded as tertiary silver particles, the average aspect ratio of the first silver particles is 2 or more, the average aspect ratio of the second silver particles is 1.5 or more and less than 2, and the average aspect ratio of the tertiary silver particles is less than 1.5, the number ratio of the first silver particles in the mixed silver powder is 0.5% or more and 5% or less, the number ratio of the second silver particles is 10% or more, and the number ratio of the tertiary silver particles is 15% or more, and the ratio satisfies the following formula (1): Ratio α = peripheral length of secondary silver particle / (long side length of secondary silver particle × 2 + short side length of secondary silver particle × 2) (1) The average value of the ratio α (also referred to as rectangularity) calculated by the above formula (1) is 0.84 or more, and polyvalent carboxylic acid is attached to the surface of at least one type of silver particle selected from the group consisting of first silver particles, second silver particles, and third silver particles. The above-mentioned mixed silver powder can reduce the resistivity of the conductive film. The reason for this is presumably that the relatively small third silver particles enter the gaps between the first silver particles, which are advantageous for reducing the resistivity in the conductive film, and the void ratio of the conductive film is reduced, and the silver powder becomes dense, resulting in a reduction in the space in the conductive film where there are no silver particles, i.e., the part with high resistance, and the resistivity is reduced. In addition, the conductive film contains second silver particles having a long side length between the first silver particles and the third silver particles, and the shape of the second silver particles is close to a rectangle, so that the first silver particles and the second silver particles and the second silver particles may come into contact with each other by a surface or line, which further reduces the void ratio of the conductive film, further reducing the part with high resistance, and thus reducing the resistivity. And, since the aspect ratio tends to be larger as the major axis is larger, the silver particles are excellent in terms of packing property and sinterability, and as a result, the conductivity of the resulting conductive film is improved. The perimeter, rectangular long side length and short side length, average aspect ratio, number ratio, and ratio α of each silver particle can be adjusted depending on the characteristics of the silver powder that can be used as a raw material, the timing of the surface treatment agent deposition treatment described below, and the type and use rate of the polyvalent carboxylic acid that can be used in the surface treatment agent deposition treatment.
[0035] <First silver particles> In the mixed silver powder of the present invention, the first silver particles are silver particles having a long side length of 3 μm or more.
[0036] In the mixed silver powder of the present invention, the average aspect ratio of the first silver particles must be 2 or more, preferably 2.3 or more, more preferably 2.5 or more, and even more preferably 3 or more. When the average aspect ratio of the first silver particles is 2 or more, the resistivity of the conductive film can be effectively reduced. On the other hand, the average aspect ratio of the first silver particles is, for example, 5 or less, or may be 4 or less, or 3.5 or less.
[0037] The average short side length of the first silver particles is, for example, 0.6 μm or more, alternatively 1.0 μm or more, or 1.3 μm or more. For example, it is 2.5 μm or less, alternatively 2.0 μm or less, or alternatively 1.9 μm or less.
[0038] The average shape factor of the first silver particles is, for example, 2 or more, optionally 2.5 or more, or optionally 3 or more, and is, for example, 6 or less, optionally 5 or less, or optionally 4 or less.
[0039] In the mixed silver powder of the present invention, the proportion of the number of first silver particles in the mixed silver powder must be 0.5% or more, preferably 1% or more, and more preferably 1.5% or more, and must be 5% or less, preferably 4% or less, and more preferably 3% or less. When the proportion of the first silver particles in the mixed silver powder is within the above range, the resistivity of the conductive film can be effectively reduced.
[0040] <Second silver particles> In the mixed silver powder of the present invention, the second silver particles are silver particles having a long side length of 0.5 μm or more and less than 3 μm.
[0041] In the mixed silver powder of the present invention, the average aspect ratio of the secondary silver particles must be 1.5 or more, preferably 1.6 or more, and more preferably 1.7 or more, and must be less than 2, and is preferably 1.95 or less, and more preferably 1.92 or less. When the average aspect ratio of the second silver particles is within the above range, the resistivity of the conductive film can be effectively reduced.
[0042] In the mixed silver powder of the present invention, the following formula (1): Ratio α = peripheral length of secondary silver particle / (long side length of secondary silver particle × 2 + short side length of secondary silver particle × 2) (1) The average value of the ratio α calculated by the above formula must be 0.84 or more, and is preferably 0.85 or more. The ratio α represents the rectangularity of the particle cross section, and the closer the value of the ratio α is to 1, the more rectangular the particle shape is. If the average value of the ratio α is 0.84 or more, the resistivity of the conductive film can be effectively reduced. On the other hand, the average value of the ratio α is equal to or less than 1, and may be, for example, equal to or less than 0.95.
[0043] The average short side length of the second silver particles is, for example, 0.3 μm or more, optionally 0.4 μm or more, or 0.5 μm or more, and is, for example, 1 μm or less, optionally 0.8 μm or less, or 0.7 μm or less.
[0044] The average shape factor of the second silver particles is, for example, 1.5 or more, optionally 1.7 or more, or optionally 2 or more, and is, for example, 3 or less, optionally 2.5 or less, or optionally 2.3 or less.
[0045] In the mixed silver powder of the present invention, the proportion of secondary silver particles in the mixed silver powder must be 10% or more, and preferably 30% or more. When the proportion of secondary silver particles in the mixed silver powder is 10% or more, the resistivity of the conductive film can be effectively reduced.
[0046] <Tertiary silver particles> In the mixed silver powder of the present invention, the third silver particles are silver particles having a long side length of less than 0.5 μm.
[0047] In the mixed silver powder of the present invention, the average aspect ratio of the third silver particles must be less than 1.5, preferably 1.4 or less, and more preferably 1.35 or less. When the average aspect ratio of the third silver particles is less than 1.5, the resistivity of the conductive film can be effectively reduced. On the other hand, the average aspect ratio of the third silver particles is, for example, 1.1 or more, optionally 1.2 or more, or optionally 1.25 or more.
[0048] The average short side length of the silver particles is, for example, 0.1 μm or more, alternatively 0.2 μm or more, or 0.25 μm or more. For example, it is 0.5 μm or less, or 0.4 μm or less.
[0049] The average shape factor of the silver particles is, for example, 1.2 or more, optionally 1.4 or more, or optionally 1.6 or more, and is, for example, 2.5 or less, optionally 2 or less, or optionally 1.75 or less.
[0050] In the mixed silver powder of the present invention, the proportion of third silver particles in the mixed silver powder must be 10% or more, preferably 13% or more, and more preferably 15% or more. When the proportion of the third silver particles in the mixed silver powder is within the above range, the resistivity of the conductive film can be effectively reduced.
[0051] <Polycarboxylic acid> In the mixed silver powder of the present invention, a polyvalent carboxylic acid is attached to the surface of at least one type of silver particle selected from the group consisting of first silver particles, second silver particles, and third silver particles. Since the specific resistance of the conductive film can be effectively reduced, it is preferable that the mixed silver powder has a polyvalent carboxylic acid attached to the surfaces of the first silver particles and the second silver particles.
[0052] Here, the polycarboxylic acid is not particularly limited and may be any of those conventionally known. However, the polycarboxylic acid is preferably an aliphatic polycarboxylic acid, and more preferably a saturated aliphatic polycarboxylic acid, because it can effectively reduce the resistivity of the conductive film. More specifically, the polycarboxylic acid is preferably at least one polycarboxylic acid selected from the group consisting of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, malic acid, diethylglutaric acid, 3-methyladipic acid, butylmalonic acid, maleic acid, diglycolic acid, and citric acid, and is particularly preferably adipic acid.
[0053] The content ratio of the polyvalent carboxylic acid to the total of the first silver particles, the second silver particles, and the tertiary silver particles is preferably 0.01% by mass or more, and more preferably 0.02% by mass or more, and is preferably 0.15% by mass or less, more preferably 0.1% by mass or less, and even more preferably 0.05% by mass or less. When the content of the polyvalent carboxylic acid is within the above range, the resistivity of the conductive film can be effectively reduced.
[0054] <Characteristics of mixed silver powder> The cumulative 50% particle size (D) of mixed silver powder measured by laser diffraction scattering particle size distribution measurement 50 ) is, for example, 1 μm or more and, for example, 3 μm or less.
[0055] The BET specific surface area of the mixed silver powder is, for example, 0.2 m 2 / g or more, and 0.4m 2 / g or more, 0.5m2 / g or more, for example, 1m 2 / g or less, and 0.8m 2 / g or less, 0.7m 2 / g or less.
[0056] The ignition loss (Ig-Loss) value of the mixed silver powder is, for example, 0.05 mass% or more, optionally 0.1 mass% or more, or optionally 0.3 mass% or more, for example, 3 mass% or less, optionally 1 mass% or less, or optionally 0.5 mass% or less.
[0057] The tap density of the mixed silver powder is, for example, 3 g / mL or more, or may be 4 g / mL or more, or may be 5 g / mL or more, and may be, for example, 7 g / mL or less, or may be 6 g / mL or less.
[0058] (Method of manufacturing mixed silver powder) The method for producing a mixed silver powder of the present invention includes a mixing step of mixing silver powder A containing silver particles A1 and silver particles A2, and silver powder B containing silver particles B to obtain a mixture, and a pretreatment step of treating at least one of silver powder A and silver powder B with a polyvalent carboxylic acid before the mixing step to attach a surface treatment agent thereto, or a post-treatment step of treating the mixture obtained in the mixing step with a polyvalent carboxylic acid to attach a surface treatment agent thereto, wherein when 100 or more silver particles on a polished cross section of a resin block in which silver powder A is embedded in a resin, and 100 or more silver particles on a polished cross section of a resin block in which silver powder B is embedded in a resin are observed, and the perimeter of the silver particles and the long side lengths and short side lengths of a rectangle that circumscribes the outer shape of the silver particles and has the smallest area are measured, the silver particles A1 have an average aspect ratio of 2 or more, and the silver particles A2 have an average aspect ratio of less than 2, and the average aspect ratio satisfies the following formula (2): Ratio β = perimeter of silver particle A2 / (long side length of silver particle A2 × 2 + short side length of silver particle A2 × 2) (2) The average value of the ratio β (also referred to as rectangularity) calculated by the above formula is 0.84 or more, and silver particles B have an average aspect ratio of less than 1.5. According to the method for producing a mixed silver powder as described above, a mixed silver powder capable of reducing the resistivity of a conductive film can be obtained. Furthermore, according to the method for producing a mixed silver powder of the present invention, the above-mentioned mixed silver powder of the present invention can be obtained. In addition, the observation of the cross section of the silver particles in the manufacturing method of the mixed silver powder of the present invention can be carried out in the same manner as the observation of the cross section of the silver particles of the mixed silver powder of the present invention described above.
[0059] The method for producing a mixed silver powder of the present invention may further include, in addition to the above-mentioned pretreatment step, mixing step, and post-treatment step, optionally further include other steps, such as a crushing step of crushing silver particles A and / or silver particles B before the pretreatment step or the mixing step.
[0060] <Silver Powder A> Silver powder A contains silver particles A1 which have a large aspect ratio and silver particles A2 which have a smaller aspect ratio and a larger rectangular particle shape than silver particles A1.
[0061] [Silver particles A1] Silver particles A1 are silver particles having an aspect ratio of at least 2. The proportion of silver particles A1 in the silver powder A is, for example, 5% or more and 50% or less.
[0062] The average aspect ratio of silver particles A1 is 2 or more, preferably 2.3 or more, more preferably 2.5 or more, and even more preferably 3 or more. When the average aspect ratio of the silver particles A1 is 2 or more, it is possible to obtain a mixed silver powder that can effectively reduce the resistivity of a conductive film. On the other hand, the average aspect ratio of the silver particles A1 is, for example, 5 or less, or may be 4 or less, or 3.5 or less.
[0063] [Silver particles A2] Silver particles A2 are silver particles having an aspect ratio smaller than that of silver particles A1 and a rectangularity of the particle shape (ratio β described below) of 0.84 or more. Silver particles A2 are silver particles having an aspect ratio of less than 2. The rectangularities of silver particles having an aspect ratio of less than 2 are measured and the average value thereof is 0.84 or more. The proportion of silver particles A2 in silver powder A by number is preferably, for example, 50% to 95%.
[0064] The average aspect ratio of the silver particles A2 is preferably 1.4 or more and less than 2. When the average aspect ratio of the silver particles A2 is within the above range, a mixed silver powder capable of effectively reducing the resistivity of a conductive film can be obtained.
[0065] For silver powder A, the following formula (2): Ratio β = perimeter of silver particle A2 / (long side length of silver particle A2 × 2 + short side length of silver particle A2 × 2) (2) The average value of the ratio β calculated by the above formula must be 0.84 or more, and is preferably 0.85 or more. The ratio β represents the rectangularity of the particle cross section, and the closer the ratio β value is to 1, the more rectangular the particle shape is. If the average value of the ratio β is 0.84 or more, the resistivity of the conductive film can be effectively reduced. On the other hand, the average value of the ratio β is equal to or less than 1, and may be, for example, equal to or less than 0.95.
[0066] [Method of preparing silver powder A] The method for preparing silver powder A is not particularly limited as long as silver particles A and silver particles B contained in silver powder A satisfy the predetermined requirements, and any conventionally known method can be used. An example of a method for preparing silver powder A will be described below, but the silver powder A used in the method for producing a mixed silver powder of the present invention is not limited to this.
[0067] Silver powder A can be prepared by a method including the steps of: a reduction step of adding a reducing agent to an aqueous solution of a silver ammine complex to obtain a first liquid; a surface treatment agent addition step of adding a surface treatment agent to the first liquid to obtain a second liquid; a separation step of separating the spherical silver powder from the second liquid and drying it to obtain spherical silver powder having an aspect ratio of less than 1.5; and a stirring step of stirring the spherical silver powder, a lubricant, and a media in a container to partially flatten the particles to the extent that silver particles A1 have a large aspect ratio and silver particles A2 have an aspect ratio smaller than that of silver particles A1 and a greater degree of rectangularity.
[0068] - Reduction process - In the reduction step, a reducing agent is added to the aqueous silver ammine complex solution to obtain a first liquid. Here, in the reduction step, silver ions are reduced by the addition of the reducing agent, and silver particles (hereinafter referred to as core particles) can be precipitated.
[0069] Examples of the reducing agent include hydrazine, hydrazine compounds, and formalin.
[0070] The silver ammine complex aqueous solution may be prepared by adding ammonia water or an ammonium salt to a raw material solution such as a silver nitrate aqueous solution or a silver oxide suspension. A pH adjuster may be added to the raw material solution or the silver ammine complex aqueous solution. As the pH adjuster, a common acid or base may be used, such as nitric acid or sodium hydroxide.
[0071] -Surface treatment agent addition process- In the surface treatment agent addition step, a surface treatment agent is added to the first liquid obtained in the reduction step to obtain a second liquid. Here, in the surface treatment agent addition step, the surface of the core particle can be coated with the surface treatment agent by adsorption or the like. In the following, the core particles coated with the surface treatment agent are referred to as “coated particles.” The second liquid is a suspension (so-called slurry) or a dispersion liquid in which the coated particles are dispersed.
[0072] Examples of surface treatment agents include fatty acids such as stearic acid, palmitic acid, linoleic acid, linolenic acid, oleic acid, etc. Among these, unsaturated fatty acids such as linoleic acid, linolenic acid, oleic acid, etc. are preferred.
[0073] The amount of the surface treatment agent added in the surface treatment agent addition step is usually 0.05% by mass or more and 0.15% by mass or less based on the mass of silver contained in the aqueous silver ammine complex solution.
[0074] The amount of surface treatment agent that adheres to the core particles in the surface treatment agent addition step and remains after the drying step is a value measured on the spherical silver powder after the drying step described below, with the type of surface treatment agent specified. The type of surface treatment agent can be identified by qualitative analysis by gas chromatography of the surface treatment agent volatilized by heating the spherical silver powder.
[0075] The amount of the surface treatment agent attached to the spherical silver powder can be determined according to the quantitative analysis method for fatty acids described in Japanese Patent No. 5,622,543. Specifically, first, silver powder is dissolved in acid, and then an organic solvent is mixed therein. The entire amount of the surface treatment agent is extracted into the organic solvent phase. A predetermined amount of the organic solvent phase is then separated and evaporated to dryness. The carbon content of the remaining solid matter is measured using a carbon-sulfur analyzer, and the carbon content can be calculated.
[0076] For example, when the surface treatment agent is specified as stearic acid and no carbon source other than stearic acid is contained in the spherical silver powder, the method for measuring stearic acid is as follows.
[0077] When a calibration curve is obtained by measuring the carbon amount (strength) of each of standard solutions with different stearic acid contents (mg) using a carbon-sulfur analyzer, the slope of the curve is A (strength / mg). The mass X (mg) and concentration Y (%) of stearic acid in the silver powder can be calculated by the following formulas (A) and (B), respectively, when the amount of carbon obtained by measuring the remaining solid matter is C (strength) from a predetermined amount b (mL) of the treatment agent extracted into the total organic solvent amount a (mL) by the above silver powder treatment and the amount of silver powder dissolved in the acid is M (g). X(mg) = (C / A × a / b) (A) Y(%)=X / (M×1000)×100...(B)
[0078] When oleic acid is used as a treatment agent, the carbon content is measured and calculated in the same manner as above. The oleic acid concentration is also calculated using the calibration curve of stearic acid. The molecular weight of stearic acid is 284.48, with a carbon content of 216.19, and the molecular weight of oleic acid is 282.46, with a carbon content of 216.19, so the oleic acid concentration Y' can be calculated using the following formula (C). Oleic acid concentration Y' (%) = Y × (216.19 / 284.48) × (282.46 / 216.19) (C)
[0079] The amount of the surface treatment agent adhered is preferably 0.01% by mass or more and 0.11% by mass or less based on the mass of the spherical silver powder.
[0080] -Separation process- In the separation step, the coated particles are separated from the second liquid. The aggregate of coated particles separated and dried in the separation step is called spherical silver powder. In addition, the separation step may optionally include a washing and recovery step of recovering the coated particles from the second liquid and washing them, and a drying step of drying the coated particles.
[0081] In the washing and recovery step, for example, the second liquid is dehydrated to make the aggregates of the coated particles into a cake-like form, and the cake of the aggregates of the coated particles is washed. The washing in the washing and recovery step may be performed using, for example, pure water. The dehydration in the washing and recovery step may be performed by, for example, decantation or a filter press. The end point of the washing may be determined using the electrical conductivity of the washing water. Specifically, the end of the washing may be determined when the electrical conductivity of the washing water becomes equal to or lower than a predetermined value. The washed coated particles may be subjected to a drying step in an aggregated state such as a cake-like form.
[0082] In the drying step, the aggregate of coated particles containing moisture and in an agglomerated state is dried. The drying step may be performed by vacuum drying or using an airflow dryer. In the drying step, a high-pressure air flow may be blown onto the aggregate of coated particles, or the cake or silver powder in the drying process may be put into a stirrer having a stirring rotor and stirred to apply a dispersing force to the cake or silver powder in the drying process, thereby promoting dispersion or drying.
[0083] In the drying step, the temperature of the silver powder is usually not higher than 100° C. If the temperature of the silver powder is not higher than 100° C., sintering between silver particles in the silver powder can be effectively prevented.
[0084] Since the spherical silver powder after drying may be in the form of lumps, a crushing or classification operation may be carried out simultaneously with or after the drying step in order to improve the handleability of the spherical silver powder. Here, improving the handleability of the spherical silver powder means, for example, in a step (partially flattening step) described below, adding a lubricant described below, securing a degree of fluidity that does not interfere with the supply operation into the device, or loosening the spherical silver powder appropriately so that the processing in the device proceeds efficiently.
[0085] The spherical silver powder obtained in the separation step has a specific surface area diameter of 1.3 μm or more and 2.0 μm or less, calculated from the specific surface area (BET specific surface area) determined by the BET method after mixing with a lubricant described later. Here, the specific surface area diameter is the specific surface area A (m 2 / g) and the silver density ρ, using the following formula (D). Specific surface area diameter (μm)=6 / (A×ρ)...(D)
[0086] -Partial flattening process- In this process, spherical silver powder, a lubricant, and media are stirred in a container to obtain silver powder A, which is partially flattened to the extent that spherical silver powder is produced into silver particles A1 with a large aspect ratio and silver particles A2 with a small aspect ratio and large rectangularity.
[0087] Here, the partial flattening step includes a lubricant mixing step in which the spherical silver powder and the lubricant are mixed for the purpose of uniformly dispersing the lubricant on the surface of the spherical silver powder. In the lubricant mixing step, the lubricant may be added to the spherical silver powder that has been moderately disintegrated by crushing, and the lubricant may be stirred and mixed using a crusher. For example, the silver powder may be put into a Henschel type mixer (manufactured by Mitsui Mining Co., Ltd., FM mixer, model FM75 type, using SO type stirring blade) or a jet mill type mixer, the lubricant may be added, and the spherical silver powder and the lubricant may be mixed by stirring. The spherical silver powder may be in a moderately aggregated state even after the lubricant mixing step. In this step, the coated particles in the spherical silver powder after mixing with the lubricant collide with the media in the container with a small number of collisions, thereby partially flattening the particles, and silver powder A, which is an aggregate of silver particles coated with the lubricant, is obtained. Among the coated particles in the silver powder, those that have a relatively large number of collisions become silver particles A1 with a large aspect ratio, while those that have a relatively small number of collisions become silver particles A2 with a small aspect ratio and large rectangularity. The number of collisions with the media is controlled by adjusting the filling rate of the media and silver powder in the stirring vessel, and the amount of energy accumulated over time and the rotation speed of the stirring vessel so that silver particles A1 and silver particles A2 coexist (so that only silver particles A1 do not exist).
[0088] Examples of lubricants include fatty acids such as stearic acid, palmitic acid, linoleic acid, linolenic acid, and oleic acid. Among these, unsaturated fatty acids such as linoleic acid, linolenic acid, and oleic acid are preferred. The amount of lubricant added is, for example, 0.05% by mass or more and 0.3% by mass or less relative to the mass of the spherical silver powder.
[0089] For the partial flattening step, for example, a so-called media mill such as a ball mill or a bead mill may be used. Known materials such as SUS and zirconia may be used as the media. Stirring in the media mill may be performed by rotating the container or a stirring paddle, or by vibrating the container.
[0090] In addition, the partial flattening step preferably includes a step of performing a crushing process using a Henschel mixer, a jet mill mixer, or the like after the collision with the media. This crushing process crushes silver particles that have become too large due to collision with the media, and the cumulative 90% particle diameter (D 90 ), cumulative 95% particle diameter (D 95 ), and the cumulative 100% (i.e., maximum particle) particle diameter (D MAX It is also preferable to reduce the value of . Note that, in the step of performing the disintegration treatment, it is preferable to use a jet mill type mixer, since it is possible to effectively reduce the particle sizes of various particles.
[0091] When a jet mill type mixer is used in the above-mentioned disintegration step, the disintegrated silver powder may be treated in a cyclone or the like in the partial flattening step to remove small particles (such as shavings, e.g., particle size less than 0.1 μm). Note that the cyclone may be equipped with an additional airflow to increase collection efficiency.
[0092] <Silver powder B> Silver powder B is made of silver particles B.
[0093] The average aspect ratio of silver particles B must be less than 1.5, preferably 1.4 or less, and more preferably 1.35 or less. When the average aspect ratio of silver particles B is less than 1.5, a mixed silver powder capable of effectively reducing the resistivity of a conductive film can be obtained. On the other hand, the average aspect ratio of particles B is, for example, 1.1 or more, may be 1.2 or more, or may be 1.25 or more.
[0094] The average shape factor of silver particles B is, for example, 1 or more, optionally 1.3 or more, or optionally 1.5 or more, and is, for example, 1.7 or less, or optionally 1.6 or less.
[0095] The average equivalent circle diameter (Heywood diameter) of silver particles B is, for example, 0.1 μm or more, and may be 0.3 μm or more, and is, for example, 1 μm or less, and may be 0.5 μm or less.
[0096] The cumulative 50% particle size (D 50 ) is, for example, 0.3 μm or more, and may be 0.5 μm or more, and is, for example, 1.3 μm or less, and may be 1 μm or less.
[0097] The pre-treatment step, the mixing step, and the post-treatment step in the method for producing the mixed silver powder of the present invention will be described below.
[0098] <Pretreatment process> In the pretreatment step, prior to the mixing step, at least one of the silver powders A and B is treated with a polyvalent carboxylic acid to adhere a surface treatment agent thereto. Here, in the pretreatment step, it is preferable to treat the silver powder A with a surface treatment agent using a polyvalent carboxylic acid, since this makes it possible to obtain a mixed silver powder that can effectively reduce the resistivity of the conductive film.
[0099] In the pretreatment step, the treatment of adhering a surface treatment agent to the silver powder using a polyvalent carboxylic acid is not particularly limited, but can be carried out using, for example, a crusher such as a sample mill or a Henschel mixer. The time for the treatment of attaching the surface treatment agent to the silver powder using a polyvalent carboxylic acid is usually from 1 minute to 30 minutes.
[0100] The polycarboxylic acid used in the surface treatment agent attachment treatment in the pretreatment step is not particularly limited, and may be any of those conventionally known. However, since a mixed silver powder capable of effectively reducing the resistivity of the conductive film can be obtained, the polycarboxylic acid is preferably an aliphatic polycarboxylic acid, and more preferably a saturated aliphatic polycarboxylic acid. More specifically, the polycarboxylic acid is preferably at least one polycarboxylic acid selected from the group consisting of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, malic acid, diethylglutaric acid, 3-methyladipic acid, butylmalonic acid, maleic acid, diglycolic acid, and citric acid, and is particularly preferably adipic acid.
[0101] Here, the polycarboxylic acid may be used as a solution dissolved in a solvent. Examples of the solvent that can be used to dissolve the polycarboxylic acid include alcohols such as methanol, ethanol, and propanol. Among these, ethanol is preferred.
[0102] In the pretreatment step, the usage rate of polycarboxylic acid relative to the total of silver powder A and silver powder B is preferably 0.01 mass% or more, more preferably 0.02 mass% or more, preferably 0.15 mass% or less, more preferably 0.1 mass% or less, and even more preferably 0.05 mass% or less. When the content ratio of the polyvalent carboxylic acid is within the above range, a mixed silver powder capable of effectively reducing the resistivity of a conductive film can be obtained.
[0103] <Mixing process> In the mixing step, a mixture is obtained by mixing silver powder A containing silver particles A1 and silver particles A2 with silver powder B consisting of silver particles B. In addition, when a pretreatment step is performed before the mixing step, the mixture obtained in the mixing step may correspond to the target mixed silver powder.
[0104] The mixing ratio of silver powder B to silver powder A (silver powder B / silver powder A) is, for example, 10 / 90 or more, or may be 20 / 80 or more, or 30 / 70 or more, or may be, for example, 90 / 10 or less, 60 / 40 or less, or 40 / 60 or less, on a mass basis. When the mixing ratio of silver powder B to silver powder A is within the above range, a mixed silver powder capable of effectively reducing the resistivity of the conductive film can be obtained.
[0105] <Post-processing process> In the post-treatment step, the mixture obtained in the mixing step is treated with a polycarboxylic acid to adhere a surface treatment agent to the mixture. The mixture that has been treated with the surface treatment agent in the post-treatment step can correspond to the target mixed silver powder.
[0106] In the post-treatment step, the treatment of adhering the surface treatment agent to the mixture using a polyvalent carboxylic acid is not particularly limited, but can be carried out using, for example, a disintegrator such as a sample mill or a Henschel mixer. The time for the treatment of attaching the mixture to the surface treatment agent using a polyvalent carboxylic acid is usually from 1 minute to 30 minutes.
[0107] The polycarboxylic acid used in the surface treatment agent attachment treatment in the post-treatment step is not particularly limited, and may be any of those conventionally known. However, since a mixed silver powder capable of effectively reducing the resistivity of the conductive film can be obtained, the polycarboxylic acid is preferably an aliphatic polycarboxylic acid, and more preferably a saturated aliphatic polycarboxylic acid. More specifically, the polycarboxylic acid is preferably at least one polycarboxylic acid selected from the group consisting of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, malic acid, diethylglutaric acid, 3-methyladipic acid, butylmalonic acid, maleic acid, diglycolic acid, and citric acid, and is particularly preferably adipic acid.
[0108] Here, the polycarboxylic acid may be used in the form of a solution dissolved in a solvent. Examples of the solvent that can be used to dissolve the polycarboxylic acid include alcohols such as methanol, ethanol, and propanol.
[0109] In the post-treatment process, the usage rate of polycarboxylic acid relative to the total of silver powder A and silver powder B is preferably 0.01 mass% or more, more preferably 0.02 mass% or more, preferably 0.15 mass% or less, more preferably 0.1 mass% or less, and even more preferably 0.05 mass% or less. When the content ratio of the polyvalent carboxylic acid is within the above range, a mixed silver powder capable of effectively reducing the resistivity of a conductive film can be obtained.
[0110] (Conductive paste) The conductive paste of the present invention contains the above-mentioned mixed silver powder of the present invention, a binder, and a solvent, and may optionally contain components other than the mixed silver powder, the binder, and the solvent (hereinafter, these may be referred to as "other components"). Since the conductive paste of the present invention contains the mixed silver powder of the present invention, the resistivity of the conductive film can be reduced.
[0111] The content of the mixed silver powder in the conductive paste is preferably 50% by mass or more, more preferably 80% by mass or more, and is preferably 98% by mass or less, and more preferably 95% by mass or less. When the content of the mixed silver powder in the conductive paste is within the above range, the resistivity of the conductive film can be effectively reduced.
[0112] Examples of the binder for the conductive paste include epoxy resin, acrylic resin, polyester resin, polyimide resin, polyurethane resin, phenoxy resin, silicone resin, ethyl cellulose, etc. These may be used alone or in combination of two or more.
[0113] Examples of the solvent (that is, the dispersion medium) of the conductive paste include terpineol, butyl carbitol, butyl carbitol acetate, texanol, etc. These may be used alone or in combination of two or more.
[0114] Other components that the conductive paste may contain include, for example, glass frit, dispersants, surfactants, viscosity adjusters, etc. These may be used alone or in combination of two or more.
[0115] For producing the conductive paste, that is, for dispersing and kneading, ultrasonic dispersion, a disper, a three-roll mill, a ball mill, a bead mill, a two-axis kneader, a self-revolving stirrer, or the like may be used.
[0116] The viscosity of the conductive paste is not particularly limited and can be selected appropriately depending on the purpose, but under conditions of a paste temperature of 25°C and a rotation speed of 1 rpm, it is preferably 150 Pa·s or more, more preferably 200 Pa·s or more, and is preferably 800 Pa·s or less, and more preferably 750 Pa·s or less. If the viscosity of the conductive paste is 150 Pa·s or higher, the occurrence of "bleeding" during printing can be effectively suppressed. On the other hand, if the viscosity of the conductive paste is 800 Pa·s or less, the occurrence of printing unevenness can be effectively suppressed.
[0117] The conductive paste of the present invention is suitable for forming a conductive film, that is, for forming a conductive pattern on a substrate or for forming an electrode. For example, it can be applied directly to various substrates such as silicon wafers for solar cells, films for touch panels, and glass for EL devices, or can be applied or printed on a substrate on which a transparent conductive film is further provided as required, to form a conductive film. The conductive film obtained by using the conductive paste of the present invention can be suitably used for electrodes or electrical wiring applications such as collector electrodes for solar cells, external electrodes for chip-type electronic components, RFID, electromagnetic shields, vibrator bonding, membrane switches, and electroluminescence.
[0118] The conductive paste can be printed on a substrate by, for example, screen printing, offset printing, photolithography, or the like to form a conductive film in a desired shape. EXAMPLES
[0119] The present invention will be described in more detail below using examples, but the present invention is not limited to the following examples in any way.
[0120] Example 1 <Preparation of Silver Powder A> [Reduction step] First, 167.1 kg of 26 mass% ammonia aqueous solution was added to 2922 kg of silver nitrate aqueous solution containing 68.8 kg of silver as a silver ion aqueous solution to generate a silver ammine complex aqueous solution. Furthermore, 266 kg of 6 mass% hydrazine aqueous solution was added as a reducing agent to this silver ammine complex aqueous solution to obtain a first liquid. The adding rate of the reducing agent was 80 L / min.
[0121] [Surface treatment agent addition step] Five minutes after the completion of the addition of the reducing agent, 68.8 g of oleic acid (0.1 mass% relative to the mass of silver contained in the silver ammine complex aqueous solution (calculated as 68.8 g oleic acid / 68,800 g silver x 100)) was added as a surface treatment agent. After the addition of the surface treatment agent, the mixture was stirred for 5 minutes to obtain a second liquid. The second liquid was in the form of a slurry containing coated particles.
[0122] [Separation process] The second liquid was filtered, washed with water, and then dried to obtain spherical silver powder.
[0123] [Lubricant mixing process] 16.25 kg of the spherical silver powder was added to a Henschel mixer (Mitsui Mining Co., Ltd., FM mixer, model FM75, using SO-type stirring blades) and stirred at 900 rpm for 1 minute, after which 37.4 g of oleic acid (0.23 mass% relative to the mass of the spherical silver powder (calculated as 37.4 g oleic acid / 16250 g spherical silver powder x 100)) was added as a lubricant and mixed at a stirring blade speed of 2200 rpm for 20 minutes. This process was carried out in multiple batches to obtain lubricant-mixed silver powder in which the lubricant was dispersed on the surfaces of the silver particles.
[0124] [Partially flattening process] 32 kg of the above lubricant-mixed silver powder and 256 kg of SUS balls (diameter 1.6 mm) were placed in a vibration mill (Chuo Kakoki Co., Ltd., FVR-20 model) and treated for 135 minutes at a vibration frequency of 780 vpm to partially flatten the lubricant-mixed silver powder.
[0125] The partially flattened silver powder (hereinafter also referred to as secondary silver powder) was separated from the SUS balls, and then crushed by stirring at 2600 rpm for 25 minutes in the above-mentioned Henschel type mixer. Furthermore, in order to remove coarse particles from the crushed secondary silver powder, it was sieved with a dry sieving device (manufactured by Freund Turbo Corporation, TS125×200 type / 27 μm mesh screen) to obtain silver powder A.
[0126] [Cross-section observation of silver powder A] The silver particles in silver powder A were observed, and the average aspect ratio of silver particles A1 was measured by the following method, and the average aspect ratio of silver particles A2 was measured by the following method, and the average aspect ratio and the following formula (2): Ratio β = perimeter of silver particle A2 / (long side length of silver particle A2 × 2 + short side length of silver particle A2 × 2) (2) The average value of the ratio β calculated by Specifically, first, silver powder A was put into a resin (Epofix resin, manufactured by Struers) and a hardener (Epofix hardener, manufactured by Struers) and solidified, and the cross-section of the silver particles was exposed by polishing with a cross-section polisher (ArBlade5000, manufactured by Japan High-Technologies Corporation), and each silver particle was observed at 5,000 times magnification with a scanning electron microscope (JEOL JSM-IT300LV, manufactured by JEOL Ltd.). Here, based on the contrast between the insulating resin and the conductive silver particles, the outline of the silver particles is clear and the outer periphery of the silver particles is clearly visible, so that the cross-section is considered to be exposed. Then, for 100 or more silver particles arbitrarily selected from the silver particles whose outer periphery is clearly visible on the polished cross-section of the resin block in which silver powder A is embedded in the resin, the long side length, short side length, and perimeter of each silver particle were measured by tracing the outer periphery of the silver particles using image analysis software (Mac-View, image analysis type particle size distribution measurement software, manufactured by Mountec Co., Ltd.). The long side length and short side length were automatically calculated to be the value when the area of a rectangle circumscribing the outer shape of each silver particle was the smallest. Next, silver particles with an aspect ratio of 2 or more were designated as silver particles A1, and silver particles with an aspect ratio of less than 2 were designated as silver particles A2, and the average aspect ratio of silver particles A1 and the average aspect ratio and average ratio β of silver particles A2 were calculated. The results are shown in Table 1.
[0127] <Preparation of Silver Powder B> As silver powder B, "AG-2-1C" manufactured by DOWA High-Tech Co., Ltd. was prepared. The silver powder B had a volume-based cumulative 50% particle diameter (D 50 ) was 0.80 μm, and the average shape factor, measured using the image analysis particle size distribution measurement software Mac-View manufactured by Mountech Co., Ltd., was 1.53, the average aspect ratio was 1.3, and the average Heywood diameter was 0.34 μm.
[0128] <Production of mixed silver powder> [Pretreatment process] First, a solution was prepared by dissolving 0.056 g of adipic acid (manufactured by Junsei Chemical Co., Ltd.) in 0.504 g of ethanol solvent. Next, this solution was added to 120 g of the silver powder A obtained above and mixed for 4.5 minutes using a sample mill (manufactured by Kyoritsu Riko Co., Ltd., SK-M10), and the surface of the silver powder A was treated with adipic acid. Oleic acid is used as a surface treatment agent and lubricant in the manufacturing process of silver powder A, and this treatment caused adipic acid to adhere to the surface of silver powder A as an additional surface treatment agent.
[0129] [Mixing process] Silver powder A, which had been subjected to the surface treatment agent adhesion treatment obtained in the above pretreatment step, and silver powder B were mixed in a mass ratio of 60:40 (silver powder B / silver powder A=40 / 60) to produce a mixture (i.e., mixed silver powder). The resulting mixed silver powder was used to carry out the various measurements shown below. A scanning electron microscope photograph of the resulting mixed silver powder is shown in FIG. 2.
[0130] [Measurement of BET specific surface area] The BET specific surface area of the mixed silver powder obtained above was measured by the BET single-point method using nitrogen adsorption, using a BET specific surface area measuring device (Macsorb HM-model 1210, manufactured by MOUNTECH Co., Ltd.). In measuring the BET specific surface area, the degassing conditions before the measurement were 60°C and 10 minutes. The results are shown in Table 2.
[0131] [Measurement of particle size distribution] The cumulative 10% particle size (D 10 ), cumulative 50% particle diameter (D 50 ), cumulative 90% particle diameter (D 90 ), and cumulative 95% particle size (D 95 ), and the cumulative 100% (i.e., maximum particle) particle diameter (D MAX ) was measured by the following method. 50 ) for the cumulative 90% particle size (D 90 ) and cumulative 10% particle size (D 10 ) and the ratio of the difference [(D 90 -D 10 ) / D 50 The results are shown in Table 2. 0.1 g of the mixed silver powder was added to 40 mL of isopropyl alcohol (IPA) and dispersed for 2 minutes using an ultrasonic homogenizer (device name: US-150T, manufactured by Nippon Seiki Seisakusho Co., Ltd.; 19.5 kHz, tip diameter 18 mm), after which the particle size distribution was measured using a laser diffraction / scattering type particle size distribution analyzer (Microtrac MT-3300 EXII, manufactured by Microtrack-Bell Corporation).
[0132] [Measurement of Ignition Loss (Ig-Loss) Value] The ignition loss (Ig-Loss) value of the mixed silver powder obtained above was calculated by precisely weighing 3 g of the mixed silver powder sample (weighing value: w1), placing it in a magnetic crucible, heating it to 800°C, and holding it at 800°C for 30 minutes, which is a sufficient time to reach a constant weight, then cooling it and reweighing it (weighing value: w2), and calculating it from "Ig-Loss value (mass%) = (w1-w2) / w1 x 100". The results are shown in Table 2.
[0133] [Measurement of tap density] The tap density of the mixed silver powder obtained above was measured using a tap density measuring device (Shibayama Scientific Co., Ltd., bulk specific gravity measuring device SS-DA-2) by weighing 30 g of silver powder, placing it in a 20 mL test tube, tapping it 1,000 times with a drop of 20 mm, and calculating it from "tap density = sample mass (g) / sample volume after tapping (mL)". The results are shown in Table 2.
[0134] [Cross-section observation of mixed silver powder] The silver particles in the mixed silver powder were observed and were analyzed by the following method. (A) For the mixed silver powder (whole silver particles), the overall average shape factor, the overall average long side length, the overall average short side length, and the overall average aspect ratio (B) Regarding the first silver particles, the number ratio, the average shape factor, the average short side length, and the average aspect ratio (C) Regarding the second silver particles, the number ratio, the average value of the shape factor, the average value of the short side length, and the average value of the aspect ratio, and the following formula (1): Ratio α = peripheral length of secondary silver particle / (long side length of secondary silver particle × 2 + short side length of secondary silver particle × 2) (1) The average value of the ratio α calculated by (D) Regarding the tertiary silver particles, the number ratio, the average shape factor, the average short side length, and the average aspect ratio was calculated. Specifically, the mixed silver powder was first placed in a resin (Epofix resin, manufactured by Struers) and a hardener (Epofix hardener, manufactured by Struers) and solidified, then polished with a cross-section polisher (ArBlade5000, manufactured by Japan High-Technologies Corporation) to expose the cross-sections of the silver particles, and each silver particle was observed at 5,000x magnification (3,000x magnification in the case of Comparative Example 3 described below) with a scanning electron microscope (JEOL JSM-IT300LV, manufactured by JEOL Ltd.). Here, silver particles in which the outline of the silver particle is clear and the periphery of the silver particle can be clearly seen due to the contrast between the insulating resin and the conductive silver particles are deemed to have an exposed cross-section. Then, on the polished cross section of the resin block in which the mixed silver powder was embedded in the resin, 100 or more silver particles were arbitrarily selected from the silver particles whose periphery was clearly visible, and the long side length, short side length, perimeter, area, and maximum length of each silver particle were measured by tracing the periphery of the silver particles using image analysis software (Mac-View, image analysis type particle size distribution measurement software manufactured by Mountec Co., Ltd.). The long side length and short side length were automatically calculated as the value when the area of the rectangle circumscribing the outer shape of each silver particle was the smallest. Using these measured values, the overall average shape factor, the overall average long side length, the overall average short side length, and the overall average aspect ratio were calculated for (A) mixed silver powder (all silver particles). The results are shown in Table 2. Next, silver particles with a long side length of 3 μm or more are called first silver particles, silver particles with a long side length of 0.5 μm or more and less than 3 μm are called second silver particles, and silver particles with a long side length of less than 0.5 μm are called third silver particles. (B) Regarding the first silver particles, the number ratio, the average shape factor, the average short side length, and the average aspect ratio (C) Regarding secondary silver particles, the number ratio, the average shape factor, the average short side length, the average aspect ratio, and the average ratio α (D) Regarding the tertiary silver particles, the number ratio, the average shape factor, the average short side length, and the average aspect ratio The results are shown in Table 2.
[0135] <Preparation of conductive paste> The mixed silver powder obtained above was mixed by stirring for 30 seconds at 1200 rpm using a propellerless rotary type stirring and degassing device (VMX-N360 made by EME Corporation) so that the conductive paste contained 91 mass% Ag, 3.8 mass% epoxy resin A (EP4901E made by ADEKA), 1.0 mass% epoxy resin B (jER1009 made by Mitsubishi Chemical), 0.2 mass% curing agent (boron trifluoride monoethylamine complex made by Wako Pure Chemical Industries), and 4.0 mass% solvent (BCA: butyl carbitol acetate), and then the mixture was kneaded by passing it through a three-roll machine (80S made by EXAKT) with a roll gap of 100 μm to 20 μm to obtain a conductive paste. The viscosity of the obtained conductive paste was measured and adjusted to 300 Pa s using BCA. The viscosity of the conductive paste was measured using a viscometer (Brookfield DV-III, CP-52 cone) at 25°C and 1 rpm after holding for 5 minutes.
[0136] <Conductive film formation> The conductive paste obtained above was printed with a screen printer (Microtec MT-320T) under a squeegee pressure of 0.18 MPa to form a line pattern with a width of 500 μm and a length of 37.5 mm to form a conductive paste film. The film obtained was then heat-cured at 200° C. for 30 minutes using an air circulation dryer to form a conductive film.
[0137] [Resistivity value] The average thickness of the conductive film was measured by measuring the step between the conductive film and the non-printed portion of the alumina substrate using a surface roughness meter (Surfcom 480B-12 manufactured by Tokyo Seimitsu Co., Ltd.). The resistance of the conductive film was then measured using a digital multimeter (R6551 manufactured by ADVANTEST Co., Ltd.). The volume of the conductive film was calculated from the size of the conductive film (average thickness, width, length), and the specific resistance was calculated from this volume and the measured resistance. The results are shown in Table 2.
[0138] Example 2 Except for the fact that the mixed silver powder was produced by the following method, various operations and measurements were carried out in the same manner as in Example 1. The results are shown in Tables 1 and 2. A scanning electron microscope photograph of the obtained mixed silver powder is shown in FIG.
[0139] <Production of mixed silver powder> [Pretreatment process] Silver powder B was prepared as "AG-2-1C" and was subjected to a surface treatment using adipic acid. The volume-based cumulative 50% particle diameter (D 50 ) was 0.80 μm, and the average shape factor, measured using the image analysis particle size distribution measurement software Mac-View manufactured by Mountech Co., Ltd., was 1.53, the average aspect ratio was 1.3, and the average Heywood diameter was 0.34 μm. For the surface treatment agent attachment treatment using adipic acid, first, a solution was prepared by dissolving 0.084 g of adipic acid (manufactured by Junsei Chemical Co., Ltd.) in 0.756 g of ethanol solvent. Next, this solution was added to 120 g of "AG-2-1C" and mixed for 4.5 minutes using a sample mill (manufactured by Kyoritsu Riko Co., Ltd., SK-M10), and the surface of Silver Powder B was treated with adipic acid.
[0140] [Crushing process] First, 120 g of silver powder A obtained by the same method as the preparation method of silver powder A in Example 1 above was pulverized for 4.5 minutes using a sample mill (SK-M10, manufactured by Kyoritsu Riko Co., Ltd.).
[0141] [Mixing process] Silver powder A obtained in the above-mentioned crushing step and silver powder B that had been treated with a surface treatment agent were mixed in a mass ratio of 60:40 (silver powder B / silver powder A=40 / 60) to produce a mixture (i.e., mixed silver powder).
[0142] Example 3 Except for the fact that the mixed silver powder was produced by the following method, various operations and measurements were carried out in the same manner as in Example 1. The results are shown in Tables 1 and 2. A scanning electron microscope photograph of the obtained mixed silver powder is shown in FIG.
[0143] <Production of mixed silver powder> [Mixing process] First, 72 g of silver powder A obtained by the same method as the preparation method of silver powder A in Example 1 above and 48 g of silver powder B were mixed to obtain a mixture.
[0144] [Post-processing process] A solution was prepared by dissolving 0.0336 g of adipic acid (manufactured by Junsei Chemical Co., Ltd.) in 0.3024 g of ethanol solvent. This solution was then added to 120 g of the mixture obtained in the above mixing step, and mixed for 7.5 minutes using a sample mill (manufactured by Kyoritsu Riko Co., Ltd., SK-M10), and the surface of the mixture was treated with adipic acid to produce a mixed silver powder.
[0145] Comparative Example 1 Various operations and measurements were carried out in the same manner as in Example 1, except that without mixing silver powder B, 120 g of silver powder A was taken, a solution of adipic acid (0.0336 g of adipic acid manufactured by Junsei Chemical Co., Ltd.) dissolved in 0.3024 g of ethanol solvent was added, and the mixture was mixed for 4.5 minutes using a sample mill to adhere adipic acid to the silver powder surface as an additional surface treatment agent. The results are shown in Tables 1 and 2. A scanning electron microscope photograph of the resulting mixed silver powder is shown in FIG.
[0146] Comparative Example 2 Except for the fact that the mixed silver powder was produced by the following method, various operations and measurements were carried out in the same manner as in Example 1. The results are shown in Tables 1 and 2. A scanning electron microscope photograph of the obtained mixed silver powder is shown in FIG.
[0147] <Production of mixed silver powder> [Crushing process] First, 120 g of silver powder A obtained by the same method as the preparation method of silver powder A in Example 1 above was pulverized for 4.5 minutes using a sample mill (SK-M10, manufactured by Kyoritsu Riko Co., Ltd.).
[0148] [Mixing process] The silver powder A obtained in the above-mentioned crushing step and the silver powder B were mixed in a mass ratio of 60:40 (silver powder B / silver powder A=40 / 60) to produce a mixture (i.e., mixed silver powder).
[0149] Comparative Example 3 In Example 1, no surface treatment agent was added in the surface treatment agent addition step, the second liquid was filtered, washed with water, and dried, and then heat-treated at 150°C for 10 hours to promote aggregation between particles, the amount of lubricant added in the lubricant mixing step was 48.8 g (0.30 mass% relative to the mass of the silver powder provided to the lubricant mixing step), the partial flattening step was performed as follows, and the mixed silver powder was produced by the following method. Various operations and measurements were performed in the same manner as in Example 1. The results are shown in Tables 1 and 2. Also, a scanning electron microscope photograph of the obtained mixed silver powder is shown in FIG. 7. Note that, for cross-sectional observation of the mixed silver powder in Comparative Example 3, each silver particle was observed at 3,000 times magnification using a scanning electron microscope.
[0150] [Partially flattening process] 32 kg of the lubricant-mixed silver powder and 256 kg of SUS balls (diameter 1.6 mm) were placed in a vibration mill (Chuo Kakoki Co., Ltd., FVR-20 type) and treated for 120 minutes at a vibration frequency of 1200 vpm as a partial flattening treatment, thereby obtaining a second silver powder by partially flattening the lubricant-mixed silver powder. Since the vibration frequency was higher than in Example 1, the flattening was more advanced than in Example 1, and the number of silver particles with a large aspect ratio was increased.
[0151] The silver(II) powder was separated from the SUS balls and then crushed by stirring at 2600 rpm for 25 minutes in the above-mentioned Henschel type mixer. In order to remove coarse particles from the crushed silver(II) powder, the powder was sieved using a dry sieving device (manufactured by Freund Turbo Corporation, TS125×200 type / 27 μm mesh screen) to obtain silver powder A.
[0152] <Production of mixed silver powder> [Pretreatment process] "AG-2-1C" was prepared as silver powder B, and a surface treatment agent was applied to it using adipic acid. For the surface treatment agent attachment treatment using adipic acid, first, a solution was prepared by dissolving 0.084 g of adipic acid (manufactured by Junsei Chemical Co., Ltd.) in 0.756 g of ethanol solvent. Next, this solution was added to 120 g of "AG-2-1C" and mixed for 4.5 minutes using a sample mill (manufactured by Kyoritsu Riko Co., Ltd., SK-M10), and the surface of Silver Powder B was treated with adipic acid.
[0153] [Mixing process] The silver powder A obtained above and silver powder B that had been treated with a surface treatment agent were mixed in a mass ratio of 60:40 (silver powder B / silver powder A=40 / 60) to produce a mixture (i.e., mixed silver powder).
[0154] [Table 1]
[0155] [Table 2]
[0156] As is clear from Table 2, the mixed silver powders of Examples 1 to 3 are capable of reducing the specific resistance of the conductive film compared to the mixed silver powders of Comparative Examples 1 to 3.
[0157] In addition, the content of adipic acid in the mixed silver powder was measured by the following method. 0.1g to 0.2g of sample silver powder was weighed out, 1mL of Hydrogen Chloride-Methanol Reagent (5-10%) [for Esterification] (Tokyo Chemical Industry Co., Ltd.) was added as a methylation reagent using a measuring pipette, and the mixture was irradiated with ultrasonic waves for 1 minute and heated in a 50°C water bath for 30 minutes. Next, the mixture was irradiated with ultrasonic waves for 1 minute, and the adipic acid eluted by these processes was methylated to produce dimethyl adipate. Next, 5 mL of hexane and 4 mL of distilled water were added to the sample solution after methylation was completed, and dimethyl adipate was extracted into the organic solvent (hexane) by performing 1-minute shaking extraction four times. Then, using methyl arachidate as an internal standard, hexane was added to the organic solvent into which dimethyl adipate had been extracted to a constant volume of 25 mL, and this was measured using a gas chromatographic quantitative analyzer GC-MS (GC: Agilent Technologies 7980B, MS: Agilent Technologies 5977B) by the MS ionization EI method, and the amount of adipic acid was calculated by conversion calculation from the amount of dimethyl adipate obtained. The amount of adipic acid (mass%) contained in the sample silver powder was quantified by comparing this calculated amount of adipic acid with the amount of sample silver powder.
[0158] When the amount of adipic acid contained in the mixed silver powder was examined using this method for measuring the content ratio of adipic acid, it was 0.021% by mass in Example 1, 0.023% by mass in Example 2, 0.024% by mass in Example 3, 0.025% by mass in Comparative Example 1, and 0.022% by mass in Comparative Example 3. It was 0.001% by mass or less in Comparative Example 2, where no adipic acid was added.
[0159] Example 4 Various operations and measurements were carried out in the same manner as in Example 1, except that the partial flattening step in the preparation of silver powder A and the production of the mixed silver powder were carried out by the following methods. The results are shown in Tables 3 and 4. A scanning electron microscope photograph of the obtained mixed silver powder is shown in Figure 8.
[0160] <Preparation of Silver Powder A> [Partially flattening process] 32 kg of the above lubricant-mixed silver powder and 256 kg of SUS balls (diameter 1.6 mm) were placed in a vibration mill (Chuo Kakoki Co., Ltd., FVR-20 model) and treated for 135 minutes at a vibration frequency of 780 vpm to partially flatten the lubricant-mixed silver powder.
[0161] The partially flattened silver powder was separated from the SUS balls and then mixed in a jet mill type mixer (Nisshin Engineering Jet Mill CJ-25) with compressed air (0.7 MPa) supplied per 1 kg of silver powder at a rate of 11.6 m 3 The crushed silver powder was then fed to a cyclone under the condition of 46 m3 of air per kg of silver powder. 3 The silver powder was treated under the above conditions, and small particles (shavings, for example, particle size less than 0.1 μm) were removed from the crushed silver powder. A device that adds an additional air flow to the cyclone to improve collection efficiency may be used.
[0162] <Production of mixed silver powder> [Mixing process] 84 g of the silver powder A obtained above and 36 g of silver powder B were mixed together to obtain a mixture.
[0163] [Post-processing process] A solution was prepared by dissolving 0.0336 g of adipic acid (manufactured by Junsei Chemical Co., Ltd.) in 0.3024 g of ethanol solvent. This solution was then added to 120 g of the mixture obtained in the above mixing step, and mixed for 4.5 minutes using a sample mill (manufactured by Kyoritsu Riko Co., Ltd., SK-M10), and the surface of the mixture was treated with adipic acid to produce a mixed silver powder.
[0164] Comparative Example 4 Various operations and measurements were carried out in the same manner as in Example 4, except that without mixing silver powder B, 120 g of silver powder A was taken, a solution of adipic acid (0.0336 g of adipic acid manufactured by Junsei Chemical Co., Ltd.) dissolved in 0.3024 g of ethanol solvent was added, and the mixture was mixed for 4.5 minutes using a sample mill to adhere adipic acid to the silver powder surface as an additional surface treatment agent. The results are shown in Tables 3 and 4. Also, a scanning electron microscope photograph of the obtained mixed silver powder is shown in FIG.
[0165] Comparative Example 5 Various operations and measurements were carried out in the same manner as in Example 4, except that the mixed silver powder was produced by the following method. The results are shown in Tables 3 and 4. A scanning electron microscope photograph of the obtained mixed silver powder is shown in FIG.
[0166] <Production of mixed silver powder> [Crushing process] First, 120 g of silver powder A obtained by the same method as the preparation method of silver powder A in Example 4 above was pulverized for 4.5 minutes using a sample mill (SK-M10, manufactured by Kyoritsu Riko Co., Ltd.).
[0167] [Mixing process] The silver powder A obtained in the above-mentioned crushing step and the silver powder B were mixed in a mass ratio of 70:30 (silver powder B / silver powder A=30 / 70) to produce a mixture (i.e., mixed silver powder).
[0168] [Table 3]
[0169] [Table 4]
[0170] As is clear from Table 4, the mixed silver powder of Example 4 can reduce the specific resistance of the conductive film compared to the mixed silver powders of Comparative Examples 4 and 5.
[0171] Furthermore, when the amount of adipic acid contained in the mixed silver powder was examined using the above-mentioned method for measuring the content ratio of adipic acid, it was 0.026% by mass in Example 4 and 0.026% by mass in Comparative Example 4. It was 0.001% by mass or less in Comparative Example 5, in which adipic acid was not added. [Industrial Applicability]
[0172] According to the present invention, a mixed silver powder capable of reducing the resistivity of a conductive film can be provided. Furthermore, according to the present invention, a method for producing a mixed silver powder capable of reducing the resistivity of a conductive film can be provided. Moreover, according to the present invention, a conductive paste capable of reducing the resistivity of a conductive film can be provided.
Claims
1. A mixed silver powder comprising first silver particles, second silver particles, and third silver particles, Observing 100 or more silver particles on a polished cross section of a resin block in which the mixed silver powder is embedded in resin, The perimeter of the silver particle; and When the long side length and the short side length of a rectangle that circumscribes the outer shape of the silver particles and has the smallest area are measured, The silver particles having a long side length of 3 μm or more are called first silver particles. The silver particles having a long side length of 0.5 μm or more and less than 3 μm are called second silver particles. The silver particles having a long side length of less than 0.5 μm are called third silver particles. In this case, the first silver particles have an average aspect ratio of 2 or more, the average aspect ratio of the second silver particles is 1.5 or more and less than 2, the average aspect ratio of the tertiary silver particles is less than 1.5; the number ratio of the first silver particles in the mixed silver powder is 1.5% or more and 5% or less, the number ratio of the second silver particles is 10% or more, and the number ratio of the tertiary silver particles is 15% or more, The following formula (1): Ratio α=perimeter of second silver particle / (long side length of second silver particle×2+short side length of second silver particle×2) (1) The average value of the ratio α calculated by is 0.84 or more, A mixed silver powder having a polyvalent carboxylic acid attached to the surface of at least one type of silver particle selected from the group consisting of the first silver particles, the second silver particles, and the third silver particles.
2. The mixed silver powder according to claim 1 , wherein a polyvalent carboxylic acid is attached to the surfaces of the first silver particles and the second silver particles.
3. 3. The mixed silver powder according to claim 1, wherein the content of the polyvalent carboxylic acid relative to the total content of the first silver particles, the second silver particles, and the tertiary silver particles is 0.01% by mass or more and 0.15% by mass or less.
4. 3. The mixed silver powder according to claim 1, wherein the polyvalent carboxylic acid is at least one polyvalent carboxylic acid selected from the group consisting of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, malic acid, diethylglutaric acid, 3-methyladipic acid, butylmalonic acid, maleic acid, diglycolic acid, and citric acid.
5. a mixing step of mixing silver powder A containing silver particles A1 and silver particles A2 with silver powder B containing silver particles B to obtain a mixture; a pretreatment step in which at least one of the silver powders A and B is treated with a polycarboxylic acid to adhere a surface treatment agent thereto before the mixing step, or a posttreatment step in which the mixture obtained in the mixing step is treated with a polycarboxylic acid to adhere a surface treatment agent thereto; Including, Observing 100 or more silver particles on a polished cross section of a resin block in which the silver powder A is embedded in a resin, and observing 100 or more silver particles on a polished cross section of a resin block in which the silver powder B is embedded in a resin, The perimeter of the silver particle; and the long side length and the short side length of a rectangle that circumscribes the outer shape of the silver particle and has the smallest area, When measuring, The silver particles A1 have an average aspect ratio of 2 or more, The silver particles A2 have an average aspect ratio of less than 2, and The following formula (2): Ratio β = peripheral length of silver particle A2 / (long side length of silver particle A2 × 2 + short side length of silver particle A2 × 2) (2) The average value of the ratio β calculated by is 0.84 or more, The method for producing a mixed silver powder according to claim 1 , wherein the silver particles B have an average aspect ratio of less than 1.
5.
6. The pretreatment step is included, The method for producing a mixed silver powder according to claim 5 , wherein in the pretreatment step, the silver powder A is treated with the polyvalent carboxylic acid to adhere a surface treatment agent thereto.
7. The method for producing a mixed silver powder according to claim 5 or 6, wherein the usage rate of the polyvalent carboxylic acid relative to the total of the silver powder A and the silver powder B is 0.01 mass% or more and 0.15 mass% or less.
8. 7. The method for producing a mixed silver powder according to claim 5 or 6, wherein the polyvalent carboxylic acid used in the surface treatment agent adhesion treatment is at least one polyvalent carboxylic acid selected from the group consisting of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, malic acid, diethylglutaric acid, 3-methyladipic acid, butylmalonic acid, maleic acid, diglycolic acid and citric acid.
9. A conductive paste comprising the mixed silver powder according to claim 1 or 2, a binder, and a solvent.
Citation Information
Patent Citations
Thermosetting conductive paste composition
JP2011100573A
Silver paste and electronic element
JP2018055883A
Silver paste, joined body, and method for manufacturing joined body
JP2019087396A
Silver powder
JP2022186757A
